Current clinical applications of artificial intelligence in shoulder surgery: what the busy shoulder surgeon needs to know and what’s coming next - Rodrigo de Marinis, MD; Erick M. Marigi, MD; Yousif Atwan, MD, MSc; Linjun Yang, PhD; Jacob F. Oeding, MS; Puneet Gupta, BS; Ayoosh Pareek, MD; Joaquin Sanchez-Sotelo, MD, PhD; John W. Sperling, MD, MBA (JSES Reviews, Reports, and Techniques, 2023)
Background: Artificial intelligence (AI) is a continuously expanding field with the potential to transform a variety of industries—including health care—by providing automation, efficiency, precision, accuracy, and decision-making support for simple and complex tasks. Basic knowledge of the key features as well as limitations of AI is paramount to understand current developments in this field and to successfully apply them to shoulder surgery. The purpose of the present review is to provide an overview of AI within orthopedics and shoulder surgery exploring current and forthcoming AI applications. Methods: PubMed and Scopus databases were searched to provide a narrative review of the most relevant literature on AI applications in shoulder surgery. Results: Despite the enormous clinical and research potential of AI, orthopedic surgery has been a relatively late adopter of AI technologies. Image evaluation, surgical planning, aiding decision-making, and facilitating patient evaluations over time are some of the current areas of development with enormous opportunities to improve surgical practice, research, and education. Furthermore, the advancement of AI-driven strategies has the potential to create a more efficient medical system that may reduce the overall cost of delivering and implementing quality health care for patients with shoulder pathology. Conclusion: AI is an expanding field with the potential for broad clinical and research applications in orthopedic surgery. Many challenges still need to be addressed to fully leverage the potential of AI to clinical practice and research such as privacy issues, data ownership, and external validation of the proposed models.